Efektivitas Model Experiential Learning Berbantuan Flash Card terhadap Hasil Belajar IPAS - Dita Damayanti; Chairul Amriyah; Nurul Hidayah (Program Studi PGSD, Jurusan Ilmu Pendidikan, STKIP PGRI Bandar Lampung, 2026)
This study was motivated by the low IPAS learning outcomes of third-grade students at MIN 2 Lampung Barat due to learning activities that lacked direct student involvement and learning experiences. This study aimed to determine the effectiveness of the experiential learning model assisted by flash card media on students’ IPAS learning outcomes. The study employed a quantitative approach with a quasi-experimental method using a non-equivalent control group design. The sample consisted of 25 students in the experimental class and 27 students in the control class. Data were collected through pretest and posttest instruments and analyzed using the independent sample t-test and N-Gain test. The results showed that the experiential learning model assisted by flash card media had a significant effect on students’ learning outcomes, indicated by a significance value of 0.005 < 0.05. The average N-Gain score of the experimental class was 73.6% in the high category. Therefore, the experiential learning model assisted by flash card media was effective in improving students’ IPAS learning outcomes.